The Killing of Jean Charles de Menezes: Hyper-Militarism in the Neoliberal Economic Free-Fire Zone - McCulloch, Jude (Social justice, 2006)
Part of a special issue on deaths in custody and detention. The writers discuss the circumstances of the fatal shooting on July 22, 2005, of Brazilian electrician Jean Charles de Menezes on a tube station in South London and the incorporation of police firearm tactics from Northern Ireland and Israel. They assert that domestic mobilizations of preemptive firearms tactics used in the “war on terror” imply significant continuities with tactics used in colonial contexts that consolidate and intensify the already established trend toward more military styles of policing in liberal democracies. They contend that the underlying military philosophy collapses the idea of suspect identity with guilty acts to sanction race-based coercion and punishment, including extrajudicial killings.